Computational econophysics simulation of stock price variation influenced by sinusoidal-like economic cycle - Laosiritaworn Y. (2017)
In this work, the impact of economic cycle on a stock price was investigated via the excess demand and supply. The economic cycle was treated as external influence which determines how the investor takes his decision on trading. The external influence was prototypically prescribed as a sinusoidal function, where excess demand and supply were calculated using Ising Hamiltonian and the mean-field technique in Econophysics. The fourth order Runge Kutta was used to extract the investors' demand/supply as well as the stock price as a function of time. From the results, it is found that the external influence characteristic and market temperature have significant effect on the price changes, resulting in different characteristic of price return distribution. Specifically, lower external influence period broadens the return distribution, whereas larger market temperature results in an opposite way. This work therefore serves as an elementary base of modeling stock price when considering the external influence as dynamically changeable periodic parameters, and suggest how price and price return would react to this active behavior of the economic cycle.